Edge-wise funnel output synchronization of heterogeneous agents with relative degree one - Lee, J. G.; Berger, Thomas; Trenn, S.; Shim, H. (Automatica)

Energy-Efficient Rate Splitting for MIMO STAR-RIS-Assisted Broadcast Channels with I/Q Imbalance - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard (2023 31st European Signal Processing Conference (EUSIPCO))

SNR Maximization in Beyond Diagonal RIS-Assisted Single and Multiple Antenna Links - Santamaria, Ignacio; Soleymani, Mohammad; Jorswieck, Eduard; Gutiérrez, Jesús (IEEE Signal Processing Letters)
Keywords: Applied Mathematics; Electrical and Electronic Engineering; Signal Processing

Optimization of Rate-Splitting Multiple Access in Beyond Diagonal RIS-assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Clerckx, Bruno (IEEE Transactions on Wireless Communications)
Keywords: Applied Mathematics; Electrical and Electronic Engineering; Computer Science Applications

NOMA-Based Improper Signaling for Multicell MISO RIS-Assisted Broadcast Channels - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Rezvani, Sepehr (IEEE Transactions on Signal Processing)
Keywords: Electrical and Electronic Engineering; Signal Processing

Spectral and Energy Efficiency Maximization of MISO STAR-RIS-Assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Interference Leakage Minimization in RIS-Assisted MIMO Interference Channels - Santamaria, Ignacio; Soleymani, Mohammad; Jorswieck, Eduard; Gutiérrez, Jesús (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Developing a deep canonical correlation-based technique for seizure prediction - Vieluf, Solveig; Hasija, Tanuj; Kuschel, Maurice; Reinsberger, Claus; Loddenkemper, Tobias (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

Geodesic-Based Relaxation For Deep Canonical Correlation Analysis - Kuschel, Maurice; Marrinan, Timothy; Hasija, Tanuj (2023 IEEE 33rd International Workshop on Machine Learning for Signal Processing (MLSP))

Online system identification and excitation for thermal monitoring of electric machines using machine learning and model predictive control - Gedlu, Emebet Gebeyehu; Wallscheid, Oliver; Böcker, Joachim; Nelles, Oliver (2023 IEEE 14th International Symposium on Diagnostics for Electrical Machines, Power Electronics and Drives (SDEMPED))

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Secur. Priv.)

"We’ve Disabled MFA for You": An Evaluation of the Security and Usability of Multi-Factor Authentication Recovery Deployments - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Krause, Alexander; Simko, Lucy; Acar, Yasemin; Fahl, Sascha (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security, CCS 2023, Copenhagen, Denmark, November 26-30, 2023)

Security, Privacy, and Data-sharing Trade-offs When Moving to the United States: Insights from a Qualitative Study - Tran, Mindy; Munyendo, Collins W; Sri Ramulu, Harshini; Rodriguez, Rachel Gonzalez; Schnell, Luisa Ball; Sula, Cora; Simko, Lucy; Acar, Yasemin (2024 IEEE Symposium on Security and Privacy (SP))

"We’ve Disabled MFA for You": An Evaluation of the Security and Usability of Multi-Factor Authentication Recovery Deployments - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Krause, Alexander; Simko, Lucy; Acar, Yasemin; Fahl, Sascha (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Security & Privacy)

The Use and Non-Use of Technology During Hurricanes - Simko, Lucy; Sri Ramulu, Harshini; Kohno, Tadayoshi; Acar, Yasemin (Proc. ACM Hum. Comput. Interact.)

Neue Wege im mathematischen Unterricht: Auf den Spuren Mathilde Vaertings - Werth, Gerda

Standardkonstruktionen eigenständig entdecken. Mathilde Vaertings Idee der Selbstständigkeitsprobe - Werth, Gerda (mathematik lehren)

$L^2$-spectrum, growth indicator function and critical exponent on locally symmetric spaces - Wolf, Lasse L.; Zhang, Hong-Wei (arXiv:2311.11770)
In this short note we observe, on locally symmetric spaces of higher rank, a connection between the growth indicator function introduced by Quint and the modified critical exponent of the Poincar\'e series equipped with the polyhedral distance. As a consequence, we provide a different characterization of the bottom of the $L^2$-spectrum of the Laplace-Beltrami operator in terms of the growth indicator function. Moreover, we explore the relationship between these three objects and the temperedness.

JuGaze: A Cell-based Eye Tracking and Logging Tool for Jupyter Notebooks - Sparmann, Sören; Hüsing, Sven; Schulte, Carsten (Proceedings of the 23rd Koli Calling International Conference on Computing Education Research)

Resonances and Weighted Zeta Functions for Obstacle Scattering via Smooth Models - Delarue, Benjamin; Schütte, Philipp; Weich, Tobias (Annales Henri Poincaré)
Abstract We consider a geodesic billiard system consisting of a complete Riemannian manifold and an obstacle submanifold with boundary at which the trajectories of the geodesic flow experience specular reflections. We show that if the geodesic billiard system is hyperbolic on its trapped set and the latter is compact and non-grazing, the techniques for open hyperbolic systems developed by Dyatlov and Guillarmou (Ann Henri Poincaré 17(11):3089–3146, 2016) can be applied to a smooth model for the discontinuous flow defined by the non-grazing billiard trajectories. This allows us to obtain a meromorphic resolvent for the generator of the billiard flow. As an application we prove a meromorphic continuation of weighted zeta functions together with explicit residue formulae. In particular, our results apply to scattering by convex obstacles in the Euclidean plane.
Keywords: Mathematical Physics; Nuclear and High Energy Physics; Statistical and Nonlinear Physics

Singular cohomology of symplectic quotients by circle actions and Kirwan surjectivity - Delarue, Benjamin; Ramacher, Pablo; Schmitt, Maximilian (arXiv:2312.03634)
Let $M$ be a symplectic manifold carrying a Hamiltonian $S^1$-action with momentum map $J:M → \mathbb{R}$ and consider the corresponding symplectic quotient $\mathcal{M}_0:=J^{-1}(0)/S^1$. We extend Sjamaar's complex of differential forms on $\mathcal{M}_0$, whose cohomology is isomorphic to the singular cohomology $H(\mathcal{M}_0;\mathbb{R})$ of $\mathcal{M}_0$ with real coefficients, to a complex of differential forms on $\mathcal{M}_0$ associated with a partial desingularization $\widetilde{\mathcal{M}}_0$, which we call resolution differential forms. The cohomology of that complex turns out to be isomorphic to the de Rham cohomology $H(\widetilde{ \mathcal{M}}_0)$ of $\widetilde{\mathcal{M}}_0$. Based on this, we derive a long exact sequence involving both $H(\mathcal{M}_0;\mathbb{R})$ and $H(\widetilde{ \mathcal{M}}_0)$ and give conditions for its splitting. We then define a Kirwan map $\mathcal{K}:H_{S^1}(M) → H(\widetilde{\mathcal{M}}_0)$ from the equivariant cohomology $H_{S^1}(M)$ of $M$ to $H(\widetilde{\mathcal{M}}_0)$ and show that its image contains the image of $H(\mathcal{M}_0;\mathbb{R})$ in $H(\widetilde{\mathcal{M}}_0)$ under the natural inclusion. Combining both results in the case that all fixed point components of $M$ have vanishing odd cohomology we obtain a surjection $\check κ:H^ev_{S^1}(M) → H^ev(\mathcal{M}_0;\mathbb{R})$ in even degrees, while already simple examples show that a similar surjection in odd degrees does not exist in general. As an interesting class of examples we study abelian polygon spaces.

A Riemann-Roch formula for singular reductions by circle actions - Delarue, Benjamin; Ioos, Louis; Ramacher, Pablo (arXiv:2302.09894)
We compute a Riemann-Roch formula for the invariant Riemann-Roch number of a quantizable Hamiltonian $S^1$-manifold $(M,ω,\mathcal{J})$ in terms of the geometry of its symplectic quotient, allowing $0$ to be a singular value of the moment map $\mathcal{J}:M→\mathbb{R}$. The formula involves a new explicit local invariant of the singularities. Our approach relies on a complete singular stationary phase expansion of the associated Witten integral.

Coupled CP Tensor Decomposition with Shared and Distinct Components for Multi-Task Fmri Data Fusion - Borsoi, R. A.; Lehmann, Isabell; Akhonda, M. A. B. S.; Calhoun, V. D.; Usevich, K.; Brie, D.; Adali, T. (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Deriving 3D Functional Brain Regions from Multi-Slice Functional Ultrasound Data Using ICA and IVA - Lehmann, Isabell; Adali, Tülay; Kruizinga, Pieter; Hunyadi, Borbála (2023 57th Asilomar Conference on Signals, Systems, and Computers)

Scalable Multi-FPGA Design of a Discontinuous Galerkin Shallow-Water Model on Unstructured Meshes - Faj, Jennifer; Kenter, Tobias; Faghih-Naini, Sara; Plessl, Christian; Aizinger, Vadym (Proceedings of the Platform for Advanced Scientific Computing Conference (PASC))

FPGA Acceleration for HPC Supercapacitor Simulations - Prouveur, Charles; Haefele, Matthieu; Kenter, Tobias; Voss, Nils (Proceedings of the Platform for Advanced Scientific Computing Conference (PASC))

Large-Time Behavior of Two Families of Operators Related to the Fractional Laplacian on Certain Riemannian Manifolds - Papageorgiou, Efthymia (Potential Analysis)
Abstract This note is concerned with two families of operators related to the fractional Laplacian, the first arising from the Caffarelli-Silvestre extension problem and the second from the fractional heat equation. They both include the Poisson semigroup. We show that on a complete, connected, and non-compact Riemannian manifold of non-negative Ricci curvature, in both cases, the solution with $$L^1$$ L 1 initial data behaves asymptotically as the mass times the fundamental solution. Similar long-time convergence results remain valid on more general manifolds satisfying the Li-Yau two-sided estimate of the heat kernel. The situation changes drastically on hyperbolic space, and more generally on rank one non-compact symmetric spaces: we show that for the Poisson semigroup, the convergence to the Poisson kernel fails -but remains true under the additional assumption of radial initial data.
Keywords: Analysis

Asymptotics for the infinite Brownian loop on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Elliptic and Parabolic Equations)
Abstract The infinite Brownian loop on a Riemannian manifold is the limit in distribution of the Brownian bridge of length T around a fixed origin when $$T → +∞ $$ T → + ∞ . The aim of this note is to study its long-time asymptotics on Riemannian symmetric spaces G / K of noncompact type and of general rank. This amounts to the behavior of solutions to the heat equation subject to the Doob transform induced by the ground spherical function. Unlike the standard Brownian motion, we observe in this case phenomena which are similar to the Euclidean setting, namely $$L^1$$ L 1 asymptotic convergence without requiring bi- K -invariance for initial data, and strong $$L^{∞ }$$ L ∞ convergence.
Keywords: Applied Mathematics; Numerical Analysis; Analysis

New examples of harmonic maps to the hyperbolic plane via Bäcklund transformation - Polychrou, G.; Papageorgiou, Efthymia; Fotiadis, A.; Daskaloyannis, C. (Revista Matemática Complutense)
Abstract We study harmonic maps from a subset of the complex plane to a subset of the hyperbolic plane. In Fotiadis and Daskaloyannis (Nonlinear Anal 214, 112546, 2022), harmonic maps are related to the sinh-Gordon equation and a Bäcklund transformation is introduced, which connects solutions of the sinh-Gordon and sine-Gordon equation. We develop this machinery in order to construct new harmonic maps to the hyperbolic plane.
Keywords: General Mathematics

Reducing Contact Bouncing of a Relay by Optimizing the Switch Signal During Run-Time - Winkel, Fabian; Scholz, Peter; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Automation Science and Engineering)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Strategische Planung des Einstiegs in die Plattformökonomie - Özcan, Leon; Drewel, Marvin; Koldewey, Christian; Dumitrescu, Roman (Digitalisierung: Fallstudien, Tools und Erkenntnisse für das digitale Zeitalter)

acatech Maturity Index Smart Services - Dumitrescu, Roman; Riemensperger, Frank; Schuh, Günther; Biehler, Jan; Frey, Anna; Hocken, Christian; Koldewey, Christian; Kühn, Arno; Rabe, Martin; Schacht, Maximilian; Comans, Sebastian; Fichtler, Timm; et al.

Circular Product-Service-System Ideation Canvas – A Framework for the Design of circular Product-Service-System Ideas - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Scenario-Based Foresight in the Age of Digital Technologies and AI - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (New Digital Work)

Verdoppeln und Halbieren im Zahlenraum bis 100 - Erkenntnisse einer Interviewstudie in Klasse 2 - Schwerin, Imke (Mathematikdidaktik Grundschule)

Mathematik – Lesen – Lernen: Ein Vorlesungskonzept zur Förderung mathematischer Lesekompetenz - Rezat, Sebastian; Malik, Sara Naseem; Leifeld, Markus (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 29.08.2022 bis 02.09.2022 in Frankfurt am Main)

Verstehen schriftlicher Rechenverfahren durch algorithmisches Denken am Beispiel der schriftlichen Subtraktion - Leifeld, Markus; Rezat, Sebastian (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 29.08.2022 bis 02.09.2022 in Frankfurt am Main)

Herausforderungen anwendungsbezogener Aufgaben - eine curriculare Perspektive auf den Forschungsstand - Malik, Sara Naseem; Rezat, Sebastian (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 29.08.2022 bis 02.09.2022 in Frankfurt am Main)

Toward student agency in the selection and use of digital resources for learning and studying mathematics - Pepin, Birgit; Kock, Zeger-jan; Rezat, Sebastian (Handbook of Digital Resources in Mathematics Education)

Meta-Resources: Supporting the design of mathematics teaching and learning - Gueudet, Ghislaine; Pepin, Birgit; Rezat, Sebastian (Handbook of Digital Resources in Mathematics Education)

The role of digital technologies in transforming student learning landscapes - Rezat, Sebastian; Geiger, Vince (Handbook of Digital Resources in Mathematics Education)

Geometrie: Leitidee Raum und Form - Hattermann, Mathias; Rezat, Sebastian; Sträßer, Rudolf (Handbuch der Mathematikdidaktik)

Implementing profession orientation as a design principle for overcoming Klein’s second discontinuity – preservice teacher’s perspectives on interface activities in the context of a geometry course - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Intending to counteract Klein’s second discontinuity in teacher education, we explored and applied the innovation of “interface ePortfolio” in the context of a geometry course for preservice teachers (PSTs). The tool offers the possibility of implementing the design principle of profession orientation. In the article, we theoretically clarify what we understand by this principle and locate our innovative concept against this theoretical background. We empirically investigate the extent to which counteraction against the second discontinuity is successful by analyzing reflection texts created in the interface ePortfolio, focusing on PSTs’ perspectives. Our qualitative content analysis shows that most of them perceive the innovation as helpful in the intended sense and indicates that the course concept, in general, and the interface ePortfolio, in particular, have helped establish relevant links between the course content and their later work as teachers.
Keywords: General Mathematics; Education

Sprache und Mathematiklernen - Leiss, Dominik; Gerlach, Kerstin; Wessel, Lena; Schmidt-Thieme, Barbara (Handbuch der Mathematikdidaktik)

Supporting Students in Developing Adequate Concept Images and Definitions at University: The Case of the Convergence of Sequences - Ostsieker, Laura; Biehler, Rolf (Practice-Oriented Research in Tertiary Mathematics Education)

Analyzing the Interface Between Mathematics and Engineering in Basic Engineering Courses - Kortemeyer, Jörg; Biehler, Rolf (Practice-Oriented Research in Tertiary Mathematics Education)

The use of integrals for accumulation and mean values in basic electrical engineering courses - Kortmeyer, Jörg; Biehler, Rolf (The Learning and Teaching of Calculus Across Disciplines – Proceedings of the Second Calculus Conference)

Stochastik: Leitidee Daten und Zufall - Biehler, Rolf; Engel, Joachim; Frischemeier, Daniel (Handbuch der Mathematikdidaktik)

Impacts of Digitalization on Content and Goals of Statistics Education - Biehler, Rolf; Frischemeier, Daniel; Gould, Ronald; Pfannkuch, Maxine (Handbook of Digital Resources in Mathematics Education)